2018
DOI: 10.22159/ajpcr.2018.v11i5.24145
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Fraction of Tropidia Curculioides, a Rare Orchid of Arunachal Pradesh, India: Phytochemical Profile and Marker Compounds

Abstract: Objective: Chemical profiling of the most active fraction of Tropidia curculioides, isolation and characterization of marker compounds along with the evaluation of biological activity. Methods:The most active Et 2 O fraction of roots of T. curculioides (TC) was analyzed by gas chromatography coupled with a mass selective detector. Repetitive chromatography followed by high-performance liquid chromatography of the active fraction afforded three major compounds. The structure of the compounds was established by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…The result demonstrated that the diethyl ether (Et 2 O) fraction of roots of Tc exhibited most potent antibacterial activity with MIC 125 µg/ml; antimycobacterial activity 125 µg/ml (MIC); and leishmanicidal activity of 100 µg/ml (IC 50 ) 11 . To identify the marker compounds, column chromatography of Et 2 O fraction was conducted which resulted in the isolation of three compounds viz., 4-hydroxy benzaldehyde (TcR-1), 4,4'dihydroxydiphenylmethane (TcR-2) and 3,5dihydroxy-4-methoxy benzoic acid (TcR-3) 12…”
Section: Introductionmentioning
confidence: 99%
“…The result demonstrated that the diethyl ether (Et 2 O) fraction of roots of Tc exhibited most potent antibacterial activity with MIC 125 µg/ml; antimycobacterial activity 125 µg/ml (MIC); and leishmanicidal activity of 100 µg/ml (IC 50 ) 11 . To identify the marker compounds, column chromatography of Et 2 O fraction was conducted which resulted in the isolation of three compounds viz., 4-hydroxy benzaldehyde (TcR-1), 4,4'dihydroxydiphenylmethane (TcR-2) and 3,5dihydroxy-4-methoxy benzoic acid (TcR-3) 12…”
Section: Introductionmentioning
confidence: 99%